CXCL13 Is A Biomarker Of Anti-Leucine-Rich Glioma-Inactivated Protein 1 Encephalitis Patients - Lin Y; Yang X; Lv J; Liu X; Wang S (Neuropsychiatric Disease and Treatment, 2019)
You-ting Lin,1 Xue Yang,2 Jing-wei Lv,2 Xue-wu Liu,2,* Sheng-jun Wang2,* 1Department of Neurology, Shandong Provincial Hospital, Shandong University, Ji’nan, People’s Republic of China; 2Department of Neurology, Qilu Hospital, Shandong University, Ji’nan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Sheng-jun Wang;Xue-wu LiuDepartment of Neurology, Qilu Hospital, Shandong University, 107# Wen Hua Xi Road, Ji’nan 250012, Peoples Republic of ChinaEmail junwang9999@sina.com; qiluliuym66@163.comBackground: Although antibody-mediated immune responses are considered pathogenic and responsible for neural injury in anti-leucine-rich glioma-inactivated protein 1 (anti-LGI1) encephalitis, previous studies have indicated that cytokines and chemokines might play roles in the pathogenic process by serving as B cell enhancers. In this study, we detected the profiles of cytokines and chemokines in the cerebral fluid (CSF) and serum of patients with anti-LGI1 encephalitis to identify potential biomarkers.Methods: Sixteen patients diagnosed with anti-LGI1 encephalitis and nine patients diagnosed with noninflammatory neurologic disorders were included in the study. Cytokines and chemokines including IL-6, IL-10, IL-17, CXCL12, CXCL13, BAFF and HMGB1 in serum and CSF were measured.Results: The serum and CSF levels of CXCL13 were significantly higher in patients with anti-LGI1 encephalitis (36.32±34.71 pg/mL and 2.23±2.41 pg/mL, respectively) than in controls (10.84±5.02 pg/mL and 0.34±0.21 pg/mL, respectively). There was no significant difference in serum or CSF levels of IL-6, IL-10, IL-17, CXCL12, BAFF and HMGB1 between the two groups.Conclusion: CXCL13 is a potential biomarker of active inflammation in anti-LGI1 encephalitis. The distinctive response of cytokines and chemokines might be closely linked to the mechanisms underlying this condition.Keywords: leucine-rich glioma-inactivated protein 1, CXCL13, cytokine, encephalitis, biomarker